Diasporic Chinese ventures : the life and work of Wang Gungwu - Benton, Gregor; Liu, Hong, 1962- (Chinese worlds., 2004)
This collection of essays by and about Wang Gungwu brings together some of Wang's most recent and representative writing about the ethnic Chinese outside China giving the reader a deeper understanding of his views on migration, identity, nationalism and culture, all key issues in modern Asia's transformation. The book collects interviews, speeches and essays that illustrate the development and direction of Wang's scholarship on ethnic and diasporic Chinese.